THE IMPACT OF MANDEH TOURISM DEVELOPMENT ON SOCIOECONOMIC OF LOCAL COMMUNITIES - Firdaus, Firdaus; Nofrizal, Nofrizal; Hidayah, Ahmad (Jurnal Apresiasi Ekonomi, 2023)
Tourism has grown as a new economic resource for local communities, including rural areas. Tourism's social and economic benefits have encouraged the growth and development of new tourist destinations in various places, including in the Mandeh Region. This article discusses the social and economic impacts of the Mandeh Tourism Area on local communities. The data presented in this article are data from empirical research conducted in Mandeh, Koto XI Tarusan District, Pesisir Selatan Regency. Data was collected through in-depth interviews with village government, local communities, economic actors and tourists. Researchers directly observed socio-economic activities in the Mandeh Tourism Area during the research. Written documents about the Mandeh Tourism Area, both in the form of media news, scientific writings and others are sources of data in research. The study results show that tourism in the Mandeh area has triggered changes in people's attitudes and lifestyles and perspectives on assets and opportunities. Apart from that, the presence of tourism in the Mandeh area has also provided a new source of livelihood for the community, thus creating a diversity of sources of livelihood. The diversity of sources of livelihood has increased the income and welfare of local communities.